OVERVIEW OF WORKER CHARACTERISTICS, USE OF PPE, HYGIENE OF INDIVIDUALS, AND CONTACT DERMATITIS ON METAL COATING HOUSEHOLD INDUSTRY WORKERS - Renticabella Praharanie Edytya; Lilis Sulistyorini (Universitas Airlangga, 2020)
ABSTRACTThe use of personal protective equipment and personal hygiene is a factor that affects the occurrence of contact dermatitis. The aim of this study is to describe characteristics of workers, use of PPE, personal hygiene, and contact dermatitis in workers. This research is descriptive research with cross sectional design. This research used total populated sampling with 20 respondents in metal household coating industry of Waru and Candi Subdistrict, Sidoarjo. The results showed that the majority of workers 55% were 26-35 years old, 50% with 2-3 years working years, 50% with contact frequency <150 times and >150 times, 30% with exposure time 3.25 hours/day, 5 hours/day, and 8 hours/day. The highest percentage of APD frequency glove use is often 66% of industry Y, frequency is sometimes 58% industry Z, and frequency is never 17% industry Y. The highest percentage of APD frequency boot APD often 50% in industry X and Y, frequency is sometimes 50% industry X, and the frequency is never 50% industry Y. Personal hygiene is done by 50% of industrial workers X, 17% of industrial workers Y, 58% of industrial workers Z and personal hygiene is not good done by 50% of industrial workers X, 83% Y, 42% of industrial workers Z. Contact dermatitis experienced 100% industrial workers X, 83% of industrial workers Y, and 83% of industrial workers Z in the form of skin irritation of hands and feet. The advice given is to provide counseling on matters that can cause contact dermatitis in workers. Key word : characteristics of workers, use of PPE, personal hygiene, contact dermatitis